2021
DOI: 10.3390/nu13124502
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ Perspectives on the Current Status of Partnerships between the Food Banking and Healthcare Systems to Address Food Insecurity in the U.S.

Abstract: One in eight people in the U.S. experience food insecurity (FI). To date, the food banking sector has been at the forefront of efforts to address FI, but the healthcare sector is becoming increasingly involved in such efforts. The extent of collaboration between the two sectors remains unclear. We explored food banking stakeholders’ views on the current state of partnerships between the two sectors. We used purposive sampling to recruit ten key informants for semi-structured interviews. We also conducted a nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…A recent systematic review and meta-analysis ( 5 ) demonstrated a positive effect of food prescription programs on health outcomes and the desire of clinic staff to continue these programs. As seen in our study, future sustainability efforts need to consider reimbursement for these programs by health insurance companies ( 8 ).…”
Section: Discussionmentioning
confidence: 95%
“…A recent systematic review and meta-analysis ( 5 ) demonstrated a positive effect of food prescription programs on health outcomes and the desire of clinic staff to continue these programs. As seen in our study, future sustainability efforts need to consider reimbursement for these programs by health insurance companies ( 8 ).…”
Section: Discussionmentioning
confidence: 95%
“…The Duke Health SSP program used a health system subsidiary as the backbone organization; other pilots have utilized a neutral convener [ 32 ]. Additional research is needed to identify the optimal choice for a backbone organization [ 31 ]. Other frameworks, such as those developed by the BUILD Health Challenge, [ 27 , 34 ] Robert Wood Johnson Foundation’s Aligning Systems for Health, [ 35 ] Data Across Sectors for Health, [ 36 ] and HealthBegins, [ 37 ] could also provide value for understanding how to measure direct communication and the impact of communication on CBO and health care partnership success.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, collaborative arrangements between food banks and health care providers are becoming more prevalent. Te nature of the collaboration is about triage and support clients experiencing health needs [35]. Tis partnership model may ofer a way forward in the Australian context.…”
Section: Discussionmentioning
confidence: 99%